Training and assistance for the creative team of Kucur Village to promote village potential through social media - Wawan Eko Yulianto; Melany Melany; Aditya Nirwana (University of Merdeka Malang, 2022)
The village of Kucur has a lot of potentials that can be improved further as a source of local income. Such potentials include the water park of Lembah Gunung Sari, the coffee-based products from Koperasi Kopi RTM, and the currently popular hiking and camping spot called Bukit Jabal. However, so far, the marketing of these potentials has been done minimally and in an unorganized manner. Therefore, the community service team will provide a workshop for the creative team of Kucur village, with the three groups mentioned above being the partners, to better promote their potential. To do this, the community service team simplified the basic principles in copywriting, namely the principles of Feature-Advantage-Benefit, Problem-Agitation-Solution (PAS), and audience identification in branding, conducted workshops to introduce the simplified principles and explore their own potential, created an Instagram account, and provided mentoring through WhatsApp groups. These activities took place between May and November in Kucur village. Based on the efforts made, the community service team found that the creative team now knows that they need to start exploring the advantages and benefits of their respective products and their target market before they can promote them to the public.